2012
DOI: 10.1007/s11999-012-2420-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: Lateral Retinaculum Release in Knee Arthroplasty Using a Stepwise, Outside-in Technique

Abstract: Background Lateral release of a tight lateral retinaculum in a TKA is intended to correct patellar maltracking but the widely used inside-out technique has associated risks. We describe an alternate stepwise outside-in technique, with titrated release intended to maximize the chance of preserving the superior lateral genicular artery (SLGA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Lateral retinacular release has been utilized to improve patellar tracking but it may be accompanied by wound complication and compromise of patellar vascularity and increasing the chance of osteonecrosis or loosening. 16 In our study the mean age in median parapatellar approach was 65.36 years and in the midvastus approach it was 67.16 years, in a study Lizaur et al (1984) 20 This denotes that the most of the osteoarthritis patient in this particular age group are present in India and also ready for TKA surgery. A female preponderance in the current study (m:f=24:26) amounting to 52% of all patients correlates well with numerous studies which also show a higher incidence of osteoarthritis in female gender.…”
Section: Discussionsupporting
confidence: 46%
“…Lateral retinacular release has been utilized to improve patellar tracking but it may be accompanied by wound complication and compromise of patellar vascularity and increasing the chance of osteonecrosis or loosening. 16 In our study the mean age in median parapatellar approach was 65.36 years and in the midvastus approach it was 67.16 years, in a study Lizaur et al (1984) 20 This denotes that the most of the osteoarthritis patient in this particular age group are present in India and also ready for TKA surgery. A female preponderance in the current study (m:f=24:26) amounting to 52% of all patients correlates well with numerous studies which also show a higher incidence of osteoarthritis in female gender.…”
Section: Discussionsupporting
confidence: 46%
“…Reported rates of the procedure vary substantially, between 3% and 45%. 44 Some of the concerns with this technique have been patellar avascular necrosis and fracture. 44 Bone scans showed a "cold patella" rate of 56% after lateral release, 45 but the clinical significance of this finding is unclear.…”
Section: ˚ External Rotationmentioning
confidence: 99%
“…44 Some of the concerns with this technique have been patellar avascular necrosis and fracture. 44 Bone scans showed a "cold patella" rate of 56% after lateral release, 45 but the clinical significance of this finding is unclear. Furthermore, although some authors historically associated lateral release with patellar pain, more recent evidence, including a 2014 comparative study, 46 does not support this association.…”
Section: ˚ External Rotationmentioning
confidence: 99%
“…When the pull on the patella is stronger on the lateral portion, medial tissues are strained and this results in pain and lateral subluxation of the patella. Some studies have reported a significantly higher rate of lateral retinacular release in the standard versions of MPP than MV . This is attributed to the extensive arthrotomy incision employed in the standard MPP approach, causing a complete separation of vastus medialis from its adjoining tendon on the patella.…”
Section: Discussionmentioning
confidence: 99%